RANCANG BANGUN APLIKASI SISTEM INFORMASI SEMINAR PRAKTISI POLBENG BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING - supendi, supendi; Jamaris, Muhamad; Nurjayadi, Nurjayadi; Karpen, Karpen (P3M Politeknik Negeri Bengkalis, 2024)
A practitioner seminar is an event where professionals in a specific field share their experiences and skills. The implementation of the Extreme Programming method in creating an Information System for Practitioner Seminars at Politeknik Negeri Bengkalis can be done effectively. Currently, the management of seminar data at Politeknik Negeri Bengkalis is still manual, including participant registration, attendance, and certificates. The current system results in poor data storage and the manual one-by-one distribution of seminar certificates to participants. This research aims to design and develop a system that will facilitate the management of seminar participant data. The system applied in this research is titled